Quality Control Of Electrical Panel Powder Coating Box Production Using The DMAIC Six Sigma Method at PT DMI Tangerang - Bayu, Adiyudha Krisna; Muttaqin, Aan; Khoiri, Halwa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT DMI is a company that manufactures electrical panel boxes. There are still defective products that exceed the company's target on the results of the powder coating process. The results of powder coating at PT DMI through CV XYZ. This study used the Six Sigma method with five stages including Define, Measure, Analyze, Improve, and Control (DMAIC). The results of the define phase of this study showed that there were 3 CTQs in the powder coating results. phase measure the average DPMO value is 4107.496 and the average sigma level is 4.175. the analyze phase found 4 factors of the type of defect including humans, machines, methods and machines. In the improve phase, there are 3 recommendations that have been given, namely making a 5w+1H table, SOP and DOE. the control phase will be carried out by providing this improvement proposal to each company. The results of this study were able to minimize problems that occurred with powder coating results at PT DMI.